2011
DOI: 10.1016/j.jamcollsurg.2011.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnosis of Response to Neoadjuvant Chemoradiation Therapy in Patients with Locally Advanced Rectal Cancer

Abstract: Background Pathologic complete response (pCR) to neoadjuvant chemoradiation (CRT) is an important prognostic factor in locally advanced rectal cancer. However, it is uncertain whether histopathological techniques accurately detect pCR. We tested a novel molecular approach for detecting pCR and compared it to current histopathological approaches. Study design Pre-treatment tumor biopsies and surgical specimens were collected from 96 patients with locally advanced rectal cancer treated with neoadjuvant CRT and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 46 publications
0
18
0
1
Order By: Relevance
“…This tissue is usually outside the radiation field and it is unlikely that it received the full dose of radiation, but it was exposed to chemotherapy. While we have recently shown that mutations in KRAS and p53 remain largely unchanged in rectal cancer after CRT, 56 the possibility of mutations arising due to treatment can not be totally excluded.…”
Section: Discussionmentioning
confidence: 90%
“…This tissue is usually outside the radiation field and it is unlikely that it received the full dose of radiation, but it was exposed to chemotherapy. While we have recently shown that mutations in KRAS and p53 remain largely unchanged in rectal cancer after CRT, 56 the possibility of mutations arising due to treatment can not be totally excluded.…”
Section: Discussionmentioning
confidence: 90%
“…Even pCR patients may harbor residual cancer cells, as cancer-related DNA mutations in K-ras and p53 genes were detected by polymerase chain reaction (PCR) DNA amplification. 35 Early detection of local recurrences through strict follow-up is today the main tool to grant local control.…”
Section: Discussionmentioning
confidence: 99%
“…However, the control tissue was obtained from the proximal resection margin, which is usually outside the radiation field and there is no data indicating that CNAs arise following chemotherapy treatment of normal tissue. Furthermore, we have recently shown that mutations in KRAS and TP53 , two genes which play a role in the pathogenesis of rectal cancer, remain largely unchanged after CRT in these patients (Chen et al, 2011). …”
Section: Discussionmentioning
confidence: 99%